Congenital factor XIII deficiency caused by F13A1 gene mutations presenting with intracranial hemorrhage: a case report - Wang, Hao; Yang, Ruotong; Li, Jianchang (Frontiers in Pediatrics, 2025)
This case report describes a male infant with congenital Factor XIII deficiency who presented with severe intracranial hemorrhage. The late preterm infant (36+4 weeks) exhibited early signs of bleeding, including a hematoma at an injection site and umbilical stump bleeding. At two months of age, he experienced a spontaneous, grade IV intracranial hemorrhage complicated by hydrocephalus. Notably, routine coagulation studies were within normal limits. The diagnosis was confirmed by genetic testing, which identified compound heterozygous mutations in the F13A1 gene. Management involved external ventricular drainage and regular fresh frozen plasma transfusions as replacement therapy, resulting in a favorable outcome. This case underscores that congenital FXIII deficiency should be considered in the differential diagnosis for infants presenting with unexplained perinatal bleeding or intracranial hemorrhage, especially when standard coagulation screens are normal. Early genetic testing and institution of structured replacement therapy are crucial for preventing life-threatening bleeding and improving long-term prognosis.